Organizational structure of universities. Research trends in Scopus over the last decade - Rodríguez Medero, Susana; Naranjo Llupart, María Rosa; Pelegrín Entenza, Norberto (Revista Venezolana de Gerencia, 2025)
Organizational structure (OS) is the foundation upon which organizations are built, and for universities, it also reflects their educational and social framework. This study focuses on research trends from 2014 to 2024 regarding university organizational structures (UOS). A bibliometric analysis of 647 documents retrieved from Scopus formed the basis of the methodology. This analysis employed VOSviewer to assess production, impact, and collaboration metrics, in addition to evaluating keyword co-occurrence and author co-citations. The results classify UOS as a motor theme with a growing trend, predominantly featuring authors, journals, and affiliations from the United States of America (USA), and countries from Asia and Europe. A small number of sources concentrate scientific production and although no major producers are identified, thematic leaders of collaborative nuclei are recognized for their study. The conclusions underscore the substantial interrelationship of UOS with knowledge management, human resource management, information systems, educational processes, quality assurance, and sustainability. Thus, the continued pertinence of this trend, in subsequent investigations within the realm of university and higher education, is anticipated.